KEPEMIMPINAN PEREMPUAN PADA MADRASAH ALIYAH DI KABUPATEN BONE - St Zakiah (LPPM IAIN Parepare, 2018)
This study examines the leadership of women in Madrasah Aliyah in Bone District. The purpose of this study was to determine the profile of women's leadership, the views of religious leaders and community leaders on women's leadership and the contribution of women's leadership as the head of Madrasah Aliyah. Women's leadership styles tend to be democratic. The obstacles faced by the female Madrasah Aliyah head in Bone Regency are two, namely internal barriers and external barriers. Internal obstacles come from within the madrasa itself. With capitalization and tenacity internal obstacles can be overcome. Whereas external barriers originating outside the madrasah, namely obstacles that come from the family environment of the head of the madrasah itself. The leadership of the female head of the Madrasah Aliyah received support from religious leaders and community leaders in Bone Regency. The female head of the Madrasah Aliyah contributes in the fields of education, religion and social life.